2020
DOI: 10.14814/phy2.14369
|View full text |Cite
|
Sign up to set email alerts
|

Habitual cigarette smoking attenuates shear‐mediated dilation in the brachial artery but not in the carotid artery in young adults

Abstract: In the present study, we hypothesized that habitual cigarette smoking attenuates endothelial function in the cerebral circulation as well as that of the peripheral circulation in young adults. To test this hypothesis, we measured cerebrovascular and peripheral flow‐mediated dilation (FMD) in young smokers and nonsmokers in the present study. Ten healthy nonsmokers and 10 smokers participated in the study. We measured blood velocity and diameter in the brachial artery and internal carotid artery (ICA) using Dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 49 publications
0
7
3
Order By: Relevance
“…2018a, b , 2020; Suzuki et al . 2020), the current study found no relationship between CVR of Q ICA and cFMD diameter change ( r 2 = 0.06; P = 0.46, Fig. 4 C ).…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…2018a, b , 2020; Suzuki et al . 2020), the current study found no relationship between CVR of Q ICA and cFMD diameter change ( r 2 = 0.06; P = 0.46, Fig. 4 C ).…”
Section: Discussioncontrasting
confidence: 57%
“…Lavallée et al's (2006) findings are clearly not consonant with ours, and comparison is tenuous given several differences in the methods (e.g. non-standard BA FMD and steady-state vs. transient CO 2 tests) and the complex influences on vascular function of the various pathologies present in both of the study groups (Niedermaier et al 1993;Dzau et al 1994;Costa et al 2020;Suzuki et al 2020). Nonetheless, the inclusion of a larger sample with a greater range of vascular function may advance the current findings.…”
Section: Correlational Analysescontrasting
confidence: 60%
See 2 more Smart Citations
“…When the participants arrived at the echo lab, they needed to rest in bed in a supine position for at least 10 minutes before taking measurements. After this break, we took the measurements in a room at constant temperature (23°C–25°C) [ 12 ], which are as follows.…”
Section: Methodsmentioning
confidence: 99%